The Role of Family in the Care of Pulmonary TB Patients - Namuwali, Domianus; Hara, Maria Kareri; Mau, Aemilianus; Banhae, Yulianti K.; Rindu, Yustinus (GLOBAL HEALTH SCIENCE GROUP, 2024)
Tuberculosis (TB) remains one of the leading causes of death worldwide, including in East Sumba Regency. The management of pulmonary TB requires active involvement of the patient's family in the care, particularly at Kambaniru Health Center. This research aims to identify the role of the family in the care of pulmonary TB patients at Kambaniru Health Center. The research method utilized a quantitative approach with a phenomenological approach to understand the family's role. Participants were selected through purposive sampling, and the research was conducted in July 2021. Data were analyzed through transcription, categorization, verification of interpretation, and description. The results of the research indicate that the family plays a crucial role in the care of pulmonary TB, including reducing coughing, preventing transmission, modifying the environment, accompanying patients for regular check-ups, reminding patients to take medication, and providing motivation. The family's role includes reducing coughing, preventing transmission, modifying the environment, accompanying patients for regular check-ups, reminding patients to take medication regularly, and motivating patients to adhere to medication schedules.